Asymptotic expansions of density of normalized extremes from logarithmic general error distribution. Issue 7 (3rd April 2017) - Chen, Shouquan; Du, Lingling
ABSTRACT: Logarithmic general error distribution is an extension of the log-normal distribution. In this paper, the asymptotic expansions of densities of normalized maximum from logarithmic general error distribution are derived under two different kinds of normalized constants. By applying the main results, the higher-order expansions of moments of maxima are established.